2023
DOI: 10.1097/md.0000000000035554
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width has a prognostic value for gastric cancer patients after gastrectomy: A pooling-up analysis

Ze-Lin Wen,
Xiong Zhou,
Dong Peng

Abstract: Our study aims to investigate whether preoperative red blood cell distribution width (RDW) has a prognostic value for patients after gastric cancer (GC) surgery. We searched articles in 3 databases including PubMed, Embase, and the Cochrane Library on May 16th, 2022. The prognostic indicators included overall survival (OS) and disease-free survival (DFS). RevMan 5.3 (The Cochrane Collaboration, London, United Kingdom) and Stata V16.0 were used for statistical analysis. The Risk Of Bias In Non-randomized Studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…[28] Additionally, RDW has been associated with various cancers. [6–14] However, the specific prognostic impact of RDW on HCC remains unclear, with the underlying mechanisms yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] Additionally, RDW has been associated with various cancers. [6–14] However, the specific prognostic impact of RDW on HCC remains unclear, with the underlying mechanisms yet to be fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have highlighted RDW as a potent and independent risk factor for various cancers, including breast, [ 6 , 7 ] lung, [ 8 10 ] nasopharyngeal, [ 11 ] esophageal, [ 12 ] and colorectal cancers. [ 13 , 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Complete blood count-based biomarkers have been shown to correlate well with clinical outcomes in numerous chronic [ 5 , 6 , 7 , 8 , 9 , 10 ], infectious [ 11 , 12 , 13 , 14 , 15 ], and surgical conditions [ 16 , 17 , 18 , 19 , 20 ], as well as in cancer [ 21 , 22 , 23 , 24 , 25 , 26 ]. In particular, the potential role of the red cell distribution width (RDW), a biomarker of the heterogeneity of red blood cells’ size, in predicting adverse events and survival currently represents a topic of intense research in numerous clinical conditions [ 27 , 28 ], including malignancies such as colorectal cancer [ 29 , 30 , 31 ], esophageal cancer [ 32 , 33 ], lung cancer [ 34 , 35 ], breast cancer [ 36 , 37 ], and other malignancies [ 38 , 39 , 40 , 41 , 42 ]. In addition, several studies have shown that alterations in the RDW correlate with liver function and prognosis in numerous hepatic cancer-predisposing conditions, such as hepatitis B, chronic liver disease, and fibrosis [ 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%